(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In this article, the improvement of the investment environment in our country, the creation of a favourable business environment, socio-economic reforms aimed at attracting investments, measures to organize the effective use of investments in economic sectors and the prospects of attracting investments, the way to develop economic sectors and industries through the effective use of investments trends, the impact of investments on the economy, directions of the effectiveness of investments in the development of the economy of Uzbekistan are presented.